Holmes Rolston Endowed Chair in Environmental Ethics: announced March-April 2014 - Rolston, Holmes, 1932-2025, speaker; Unidentified speaker; Colorado State University, producer (Colorado State University. Libraries, 2014)
The Holmes Rolston Endowed Chair in Environmental Ethics, made possible by donations from Holmes and Jane Rolston, and by Myra Monfort, is announced at four celebration events during March, April, and May, 2012. 1. Dinner at Jay's Bistro, with Dean Ann Gill, Holmes and Jane Rolston, Myra Monfort, and selected guests, March 11, 2014. 2. The President's Dinner for University Distinguished Professors, April 28, 2014. 3. Celebrate Colorado State, with Tony Frank, CSU President, April 29, 2014. 4. CLA Dean Ann Gill's Reception for Faculty and Staff Donors, May 7, 2014.
Produced at Colorado State University, 2014.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Colorado State University; Holmes Rolston Endowed Chair in Environmental Ethics; Rolston, Holmes, 1932-2025; environmental ethics; Celebrate Colorado State